History of the Christian church ; v.5 - Sheldon, Henry C. (Peabody, MA Hendrickson, 1988)
Contents : v.5 : The modern church ; pt 3 : 19th century. Includes bibliographical references and indexes.
Reprinted from the original edition, published 1895, Thomas Y. Crowell and Co., New York.
Keywords: Church history -- 19th century